Identification of human-wildlife interaction hotspots near riparian reserves: A case study of Beas conservation reserve, A Ramsar site - Navdeep Sood; Rohan Kumar; Swati Sharma (Environment Conservation Journal)
This study aims to identify hotspots of Human-Wildlife Interaction (HWI) near riparian reserves located in urban and agricultural landscapes. The research is based on a section of the Beas Conservation Reserve (BCR), one of the largest and most biodiverse natural heritage Ramsar sites, located in Punjab, India, contiguous with Harike Wetland and Wildlife Sanctuary, another International Ramsar Site.  The BCR's Shape Index was calculated and found to be approximately 13.05, reflecting its highly complex and ribbon-like elongated shape, indicating high edge complexity and the higher potential for Human-Wildlife Interactions (HWI). Ten key anthropogenic, environmental, and topographic influencing factors, including Euclidean distances from roads, rivers, and protected areas along with slope, temperature, precipitation, elevation, land use, land cover, humidity, and global human footprint, were analyzed using geospatial tools. These factors were standardized and integrated by applying multiple fuzzy overlay operations and varying gamma values to assess their suitability for hotspot identification. By rigorous iterative fine-tuning and comparative analysis of different fuzzy operations, fuzzy gamma with the range of 0.75–0.80 was determined to be the most effective method, yielding the highest accuracy in predicting Human-Wildlife Interaction (HWI) hotspots near riparian reserves. The results showed a high level of accuracy in identifying HWI hotspots, with a Kappa coefficient of 0.848. Field validation at identified hotspots confirmed the result’s accuracy, aligning with actual observations of the field closely. The identification of these hotspots is important in mitigating human-wildlife conflicts, efficiently managing resources, preparing for climate change, facilitating wildlife migrations, and supporting biodiversity conservation efforts. Furthermore, the study aligns with the objectives of Sustainable Development Goals by supporting the riverine ecosystems and promoting human-wildlife coexistence.